(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The research work is aimed at studying emotive-evaluative vocabulary from an anthropocentric point of view and clarifying its cognitive-pragmatic nature. Thus, the purpose of using linguistic units by a person is determined, their cognitive and pragmatic features are revealed, and the psychological, social and mental features of a linguistic person using emotive and evaluative units in discourse are determined. When describing the assessment of language from a cognitive and communicative point of view, special attention is paid to the cognitive function of a person, national and cultural characteristics. The purpose of the study is to clarify the anthropocentric nature of emotive and evaluative vocabulary in the texts of Kazakh and foreign media. The novelty of the research work is associated with a comprehensive description of the emotive and evaluative words of the Kazakh language and foreign language materials from a linguistic, cultural, cognitive and communicative point of view, a comparison of meaning and function. The linguistic units used for evaluation by representatives of different cultures, the peculiarities of perception of emotive and evaluative words of each nation will be considered. The theoretical value of the work is related to the fact that emotive-evaluative words are described from the standpoint of the anthropotopic paradigm, their cognitive, linguistic, cultural and pragmatic characteristics are comprehensively considered. The result obtained by comparing materials in Kazakh, Russian and English, the expression of emotive-evaluative words in different languages, the peculiarities of the use and acceptance of emotive-evaluative words in connection with national identity, worldview, diversity of the image of the Universe in the consciousness of each nation. At the same time, it can be used in such fields of science as psychosemantics, psychology, ethnopsychology, psychoanalysis, ethnosociology, cultural studies bordering on linguistics. Key words: emotive-evaluative vocabulary, anthropocentric paradigm, denotation, connotation, meaning.